A multivariable predictive model for trial without catheter success: integrating clinical parameters and ultrasonographic markers - Hakan Tekinaslan; Eralp Yılmazçoban; Kürsad Dönmez; Enis Mert Yorulmaz; Serkan Ozcan; Osman Köse; Sacit Nuri Görgel; Yigit Akın (Scientific Reports, 2026)
Abstract Acute urinary retention secondary to benign prostatic hyperplasia is a common urological emergency. Although a trial without catheterisation is routinely performed after initial catheterisation, predictors of successful spontaneous voiding remain inconsistent. This study evaluated the predictive value of ultrasonographic and clinical parameters for TWOC success in patients with BPH-related AUR. This retrospective observational study enrolled 202 men aged 50–79 years who presented with AUR secondary to BPH between January 2022 and March 2026. All underwent urethral catheterisation followed by a standardised TWOC protocol. Demographic, clinical, laboratory, and ultrasonographic variables, including intravesical prostatic protrusion and bladder wall thickness, were analysed using multivariable logistic regression to identify independent predictors of TWOC success. TWOC succeeded in 98 patients (48.5%) and failed in 104 (51.5%). Successful cases were characterised by significantly lower body mass index, bladder wall thickness, and IPP grade, as well as a shorter catheter duration (all p < 0.05). TWOC success rates were 71.4% for BWT < 5 mm versus 32.2% for BWT ≥ 5 mm, and declined progressively with higher IPP grades. ROC analysis yielded a BWT cutoff of 5.35 mm (sensitivity 71.2%, specificity 84.7%). Multivariable analysis confirmed lower BMI, lower IPP grade, angiotensin receptor blocker use, and lower BWT as independent predictors. The model demonstrated good discriminatory ability (AUC 0.893, 95% CI 0.849–0.938). TWOC failure was strongly associated with subsequent surgical intervention (88.5% of patients in the failure group). Incorporating these non-invasive markers into pre-TWOC assessment may help identify patients at higher risk of catheter removal failure and inform counselling on the likelihood of requiring surgical intervention; however, external validation in independent cohorts is required before clinical implementation.